Theoretical Treatment for Electron Transport throughout Molecular Wire Bridge - Al-Badry, L. F. (University of Thi-Qar Journal of Science, 2014)
In this paper we present our theoretical treatment for electron transport through one scattering region attached to donor and left lead in the left side, while in the right side it is attached to acceptor and right lead. Our treatment is based on the time-dependent Anderson – Newns Hamiltonian. The equations of motion are derived for all subsystems then the stationary state is considered to obtain analytical expression for the transmission probability as a function of system energies. The scattering region is considered as molecular wire. The subsystems eigenvalues, the coupling interaction between them as well as the leads band width all are taken into consideration and highlighted. We concluded that the variation of the number of molecules gives the molecular wire one of the most interesting functional properties, that is the molecular on-off switching.